Investigating the Relationship Between Duolingo Engagement, Learning Motivation, and Reading Proficiency among Fifth Semester Students at UIN Raden Mas Said Surakarta - Cinthya Dhea; Sujito (Fakultas Adab dan Bahasa UIN Raden Mas Said Surakarta, 2026)
This study is grounded in the Value-Expectancy Theory and Dornyei’s Motivation Theory, which explain that learners’ motivation and engagement with interactive digital tools can influence their reading performance. The study examines the effects of Duolingo usage and learning motivation on students’ English reading skills through a quantitative, multivariate correlational design. Twenty-five university students completed Likert-scale questionnaires and reading tests. The findings revealed a moderate positive correlation between Duolingo engagement and reading performance (r = 0.421, R² = 0.17, p < 0.05), indicating that increased interaction with the Duolingo application contributes to improved reading skills. Similarly, learning motivation showed a moderate positive correlation with reading performance (r = 0.500, R² = 0.25, p < 0.05), suggesting that higher motivation enhances reading comprehension. The multiple regression model (Ŷ = 10.60+ 0.047X₁ + 0.124X₂) produced an R² value of 0.263 and F = 3.940 (p = 0.034 < 0.05), indicating that both variables simultaneously contributed significantly to reading ability. The concurrent implementation of Duolingo-facilitated digital learning and a high level of learner motivation demonstrates a statistically significant positive impact on students’ English reading proficiency.